The importance of routine genetic testing in pediatric epilepsy surgery - Lena‐Luise Becker; Konstantin L. Makridis; Angela T. Abad‐Perez; Ulrich‐Wilhelm Thomale; Anna Tietze; Christian E. Elger; Denise Horn; Angela M. Kaindl (Epilepsia Open, 2024)
Abstract Genetic variants in relevant genes coexisting with MRI lesions in children with drug‐resistant epilepsy (DRE) can negatively influence epilepsy surgery outcomes. Still, presurgical evaluation does not include genetic diagnostics routinely. Here, we report our presurgical evaluation algorithm that includes routine genetic testing. We analyzed retrospectively the data of 68 children with DRE operated at a mean age of 7.8 years (IQR: 8.1 years) at our center. In 49 children, genetic test results were available. We identified 21 gene variants (ACMG III: n = 7, ACMG IV: n = 2, ACMG V: n = 12) in 19 patients (45.2%) in the genes TSC1, TSC2, MECP2, DEPDC5, HUWE1, GRIN1, ASH1I, TRIO, KIF5C, CDON, ANKD11, TGFBR2, ATN1, COL4A1, JAK2, KCNQ2, ATP1A2, and GLI3 by whole‐exome sequencing as well as deletions and duplications by array CGH in six patients. While the results did not change the surgery indication, they supported counseling with respect to postoperative chance of seizure freedom and weaning of antiseizure medication (ASM). The presence of genetic findings leads to the postoperative retention of at least one ASM. In our cohort, the International League against Epilepsy (ILAE) seizure outcome did not differ between patients with and without abnormal genetic findings. However, in the 7/68 patients with an unsatisfactory ILAE seizure outcome IV or V 12 months postsurgery, 2 had an abnormal or suspicious genetic finding as a putative explanation for persisting seizures postsurgery, and 3 had received palliative surgery including one TSC patient. This study highlights the importance of genetic testing in children with DRE to address putative underlying germline variants as genetic epilepsy causes or predisposing factors that guide patient and/or parent counseling on a case‐by‐case with respect to their individual chance of postoperative seizure freedom and ASM weaning. Plain Language Summary Genetic variants in children with drug‐resistant epilepsy (DRE) can negatively influence epilepsy surgery outcomes. However, presurgical evaluation does not include genetic diagnostics routinely. This retrospective study analyzed the genetic testing results of the 68 pediatric patients who received epilepsy surgery in our center. We identified 21 gene variants by whole‐exome sequencing as well as deletions and duplications by array CGH in 6 patients. These results highlight the importance of genetic testing in children with DRE to guide patient and/or parent counseling on a case‐by‐case with respect to their individual chance of postoperative seizure freedom and ASM weaning.